Manoeuvring simulations of Autonomous Underwater Vehicle using quaternion - Patil, Prasad Vinayak; Khan, Md. Kareem; Korulla, Manu; Nagarajan, Vishwanath; Sha, Om Prakash (Defence Science Journal, 2022)
The dynamics of an autonomous underwater vehicle (AUV), which can perform manoeuvres with pitch angles in the range of 90° is investigated in this paper. The purpose of the AUV is to perform station keeping manoeuvre at about 90° pitch angle by varying propeller revolution. The AUV is launched / retrieved in horizontal orientation. Quaternion mathematics, 4 quadrant propeller open water characteristics and PID controller for propeller revolution are incorporated in manoeuvring mathematical model for this purpose. A procedure for optimizing the gain coefficients for the PID controller is developed using the manoeuvring mathematical model. Two design configuration of the AUV are investigated, positively buoyant and negatively buoyant. It is shown that both the optimal gain coefficients for the PID controller for propeller revolution and dynamic response of the AUV are different for each design configuration.